2003
DOI: 10.1179/016164103101201076
|View full text |Cite
|
Sign up to set email alerts
|

Nocardial cerebral abscess: Report of three cases and review of the current neurosurgical management

Abstract: Nocardia asteroides cerebral abscesses are rare but challenging intracranial lesions. Early diagnosis, institution of appropriate antimicrobial therapy, lack of underlying systemic disease and limited intracranial disease are recognized factors leading to good outcome. However, the optimal treatment approach has not been established and nocardial brain abscesses have been managed either conservatively, with steroetactic aspirations or with open craniotomy and enucleation. We present three cases of Nocardia ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 8 publications
0
21
0
6
Order By: Relevance
“…The current knowledge base of bacteria that cause brain abscesses relies on cultures of pus specimens collected after neurosurgical drainage [1,27,28]. In this study, bacteria were microscopically observed in 45% of patients, whereas culturing on axenic media yielded bacteria in 80% of patients.…”
Section: Discussionmentioning
confidence: 98%
“…The current knowledge base of bacteria that cause brain abscesses relies on cultures of pus specimens collected after neurosurgical drainage [1,27,28]. In this study, bacteria were microscopically observed in 45% of patients, whereas culturing on axenic media yielded bacteria in 80% of patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, the optimal treatment approach has not been established and nocardial brain abscesses have been managed either conservatively with stereotactic aspirations or with open craniotomy and enucleation [49,63,64]. Thus, each case needs a careful multidisciplinary evaluation by the primary physician, the infectious diseases specialist, and the surgeon.…”
Section: Treatmentmentioning
confidence: 98%
“…These organisms also disseminate to other regions of the body, especially the central nervous system. Nocardial brain infections, which frequently manifest as brain abscesses [1,2], are well documented. Thus, nocardiae may be pathogens of the CNS [1e3].…”
Section: Introductionmentioning
confidence: 99%